Comparing surgical and conservative treatment approaches for perianal abscess in patients with hematologic malignancies: a comprehensive analysis - Xun Wang; Lili Pan; Yanyan Qiu; Tingbo Liu (BMC Gastroenterology)
Abstract Perianal abscess (PA) is a complication of infection in patients with hematologic malignancies. However, the simultaneous occurrence of neutropenia and increased susceptibility to bleeding pose significant challenges for surgical intervention in perianal abscesses. In this retrospective study, we sought to evaluate and compare the efficacy of pharmacological therapy and surgical intervention in the management of PA in patients with hematologic malignancies, bwtween 2015 and 2022 at the Fujian Medical University Union Hospital. In total, 53 patients were enrolled in this study, including 19 cases with surgical intervention, and 34 cases with conservative treatment. During the 60-day follow-up period, a significant improvement of symptoms or complete resolution was observed in 48 patients (90.5%). But the cure rates between the two groups showed no significant difference (p > 0.05). Additionally, the surgical group demonstrated a significantly lower recurrence rate compared to the conservative group, while there was no statistically significant disparity in recurrence rates (10.4% vs. 23.6%, p > 0.05). Patients with conservative treatment showed significantly shorter recovery time compared to patients with surgical treatment (p = 0.048). In conclusion, both conservative and surgical management approaches were safe and effective in relieving symptoms, but surgical intervention significantly decreased the recurrence rate. Therefore, consideration of surgical intervention is warranted for patients with recurrent perianal infections after conservative treatment.